Consequential Life Cycle Assessment of energy generation from waste wood and forest residues: The effect of resource-efficient additives. (20th June 2020) - Corona, Blanca; Shen, Li; Sommersacher, Peter; Junginger, Martin
Abstract: Combustion of waste wood can cause slagging, fouling and corrosion which lead to boiler failure, affecting the energy efficiency and the lifetime of the power plant. Additivation with mineral and sulfur containing additives during waste wood combustion could potentially reduce these problems. This study aims at understanding the environmental impacts of using additives to improve the operational performance of waste wood combustion. The environmental profiles of four energy plants (producing heat and/or power), located in different European countries (Poland, Austria, Sweden and Germany), were investigated through a consequential life cycle assessment (LCA). The four energy plants are all fueled by waste wood and/or residues. This analysis explored the influences of applying different additives strategies in the four power plants, different wood fuel mixes and resulting direct emissions, to the total life cycle environmental impacts of heat and power generated. The impacts on climate change, acidification, particulate matter, freshwater eutrophication, human toxicity and cumulative energy demand were calculated, considering 1 GJ of exergy as functional unit. Primary data for the operation without additives were collected from the power plant operators, and emission data for the additives scenarios were collected from onsite measurements. A sensitivity analysis was conducted on the expected increase of energy efficiency. The analysis indicated that the use of gypsum waste, halloysite and coal fly ash decreases the environmental impacts of heat and electricity produced (average of 12% decrease in all impacts studied, and a maximum decrease of 121%). The decrease of impacts is mainly a consequence of the increase of energy generation that avoids the use of more polluting marginal technologies. However, impacts on acidification may increase (up to 120% increase) under the absence of appropriate flue gas cleaning systems. Halloysite was the additive presenting the highest benefits.